Empreendedorismo e inovação: a influência das startups no crescimento econômico - Thurner, Bruno da Veiga (2015)
Innovation has been one of the main actors at the world economic scenario, serving as basis of growth and sustainability of the strongest economies around the globe. The technology evolution has help researchers in the gathering of information, as well to near markets and to improve consumer profile data. Entrepreneurs around world have gain success through innovation activities that requires high level of risk: the startups. This study aims to identify the relationship between the entities aimed at promoting innovation and the economic growth. Through statistical analysis guided by a directed study on Incubators, Technologic Parks and the GDP per capita in Brazil there were found, eighteen correlations, ten such strongly positive.